Features of pathological changes in patients with different types of pancreatic pseudocyst. - Krivoruchko, I. A.; Goncharova, N. М.; Sorokina, I. V. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. A growing number of patients with pancreatic pseudocyst on the background of acute or chronic pancreatitis or due to injury of the pancreas encourages scientists to study the etiology and pathogenesis of this disease. Objective. Тo study morphological features of various types of wall structure and adjacent parenchyma of pseudocyst using histochemical techniques. Methods. Resected pancreatic specimens taken intraoperative from 47 patients were used as a material. Results. Patients of the first group with forming acute pseudocyst on the background of acute destructive pancreatitis, characterized by severe circulatory disorders in pancreas, destructive changes of all structural components of the gland with subsequent development of reactive inflammatory response to injury in the form of diffuse or focal leukocyte infiltration of the stroma and the parenchyma and signs of original reparative process. In all patients of the second group with postnecrotic chronic pseudocyst the wall of pseudocyst was represented by granulation tissue and fibrous layer. In the surrounding pancreatic tissues it was revealed morphological signs of chronic pancreatitis with fibrotic stromal changes and chronic inflammatory infiltration, parenchymal atrophy and restructuring of false acinar lobules, metaplasia of their cell. All patients of the third group demonstrated a pronounced fibrosis of the stroma with atrophy of parenchyma and restructuring of all components of the pancreas: the formation of false acinar lobules, compensatory hypertrophy of islet apparatus, restructuring of ductal system of pancreas, formation of retention pseudocyst with a fibrous wall lined with epithelium with signs of hyperplasia and metaplasia. Conclusion. Morphological changes that occur during formation of pseudocyst lead to organ dysfunction and should be considered as an adverse pathological process that requires surgical correction.